Transcriptomic analysis of the interactions between Fibrobacter succinogenes S85, Selenomonas ruminantium PC18 and a live yeast strain used as a ruminant feed additive - Pauline Desvignes; Philippe Ruiz; Laurie Guillot; Jeanne Danon; Alexandra Durand; Martin Beaumont; Frédérique Chaucheyras-Durand; Evelyne Forano (BMC Genomics)
Abstract Background Microbes inhabiting the rumen convert fibrous plant material into usable energy for the host ruminant through a sophisticated network of microbial interactions. Metabolite crossfeeding is considered a key feature of the rumen microbiome, enhancing its stability, productivity, and efficiency in degrading plant material. This study analysed in vitro the metabolic interactions between two key rumen bacteria: the cellulolytic bacterium Fibrobacter succinogenes S85 and the saccharolytic bacterium Selenomonas ruminantium PC18. Additionally, the impact of Saccharomyces cerevisiae CNCM I-1077 on their metabolism and interactions was investigated. This strain is used as a feed additive for ruminants. Results Bacteria were cultured on either cellobiose or cellulose as carbon substrates. Interactions were studied through RNA-seq transcriptomic analysis of various microbial combinations, alongside substrate consumption and metabolite production measurements. The results revealed crossfeeding between F. succinogenes and S. ruminantium, as well as a significant upregulation of numerous F. succinogenes CAZyme genes in response to cellulose. The presence of the yeast strain under the different culture conditions induced metabolic and gene expression changes in both F. succinogenes and S. ruminantium. Notably, no lactate was detected when the yeast was added to S. ruminantium cultures or cocultures. Furthermore, the presence of bacteria influences yeast metabolism and crossfeeding between bacteria and yeast was suggested. Conclusions The findings provide deeper insight into the in vitro interactions between F. succinogenes, S. ruminantium and S. cerevisiae, highlighting possible modes of action that may explain some of the observed positive effects of yeast on rumen function in vivo. This study underscores the mutual interactions between rumen bacteria and live yeast.